2010
DOI: 10.1017/s175173110999142x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning, expression and polymorphism of the porcine apolipoprotein A5 gene in a Jinhua × Pietrain F2 reference population

Abstract: As a newly described member of the apolipoprotein gene family, apolipoprotein A5 (APOA5) has been suggested to play a key role in the triglyceride metabolism in both human and mice. The aim of this study was to identify the porcine (Sus scrofa) APOA5 gene, determine its mRNA and its mutations that are associated with lipid accumulation. The porcine APOA5 cDNA was amplified by reverse transcriptase polymerase chain reaction using the information of the mouse or other mammals. It had been determined that the ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
(31 reference statements)
1
4
0
Order By: Relevance
“…In animal, the significant association were reported between SNPs in T635C with abdominal fat weight in F2 cross of White Plymouth Rock x Silkies chicken (Yao et al, 2008). Jiang et al (2010) confirmed in pig that the significant relationship of SNPs in APOA5 gene were found with body fat deposition in F2 Jinhua x Pietrain population.Furthermore, genome wide association study revealed that APOA5 could be a positional candidate gene for fat deposition in Broiler chickens (Moreira et al, 2018). Three genes (APOA1, APOA4, and APOA5) belong to a gene family (Apolipoproteins -APO) that encodes important regulators of lipid biosynthesis and metabolism (Delgado-Lista et al, 2010).…”
Section: Discussionsupporting
confidence: 52%
“…In animal, the significant association were reported between SNPs in T635C with abdominal fat weight in F2 cross of White Plymouth Rock x Silkies chicken (Yao et al, 2008). Jiang et al (2010) confirmed in pig that the significant relationship of SNPs in APOA5 gene were found with body fat deposition in F2 Jinhua x Pietrain population.Furthermore, genome wide association study revealed that APOA5 could be a positional candidate gene for fat deposition in Broiler chickens (Moreira et al, 2018). Three genes (APOA1, APOA4, and APOA5) belong to a gene family (Apolipoproteins -APO) that encodes important regulators of lipid biosynthesis and metabolism (Delgado-Lista et al, 2010).…”
Section: Discussionsupporting
confidence: 52%
“…Therefore, enhanced APOE under testosterone deficiency in our data might amplify castration-induced VAT deposition under HFC diet. Actually, expression levels of other well-known lipoproteins for modulating triglyceride metabolism, such as APOA5 and APOC3 [29,30], were also upregulated under testosterone deficiency, although the expressions of APOC3 were not detected in IM pig groups (Table S1). In the previous study, APOE, APOC3, and APOA5 were shown to be positively associated with plasma triglyceride levels [31,32], which indicated VAT accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that such triglyceriderich lipoproteins as VLDL and chylomicron primarily transported fatty acids as triglycerides to extra-hepatic tissues where they were stored or oxidized for energy production and therefore had critical effects on the lipid metabolism related to meat quality traits. 1,7,8) ApoR is known to be a component of VLDL and chylomicrons and to contain two short consensus repeats (SCRs) 2) which play an important role as a common protein interaction module. 9) chr9:g.132356063C > T SNP in this study was located within an SCR region of ApoR and created single base mutations (TCC !…”
Section: Identification Of Non-synonymous Snp In Apormentioning
confidence: 99%
“…Some SNPs in ApoVLDL genes, encoding apolipoproteins for VLDL, have been similarly identified to have a significant association with meat quality traits; for example, C1834T SNP, which is located in 3 0 -UTR of the ApoA5 gene, has shown a significant association with the backfat thickness and leaf fat weight. 7) Intronic SNP in ApoVLDL-II gene has also been associated with multiple meat quality traits, including the intramuscular fat content. 1) SNPs in the ApoVLDL genes are therefore suggested to have broad effects on meat quality traits, although there have been few non-synonymous exonic SNPs which may influence the structural architechure of ApoVLDL.…”
Section: Identification Of Non-synonymous Snp In Apormentioning
confidence: 99%